Evidence for increased SOX3 dosage as a risk factor for X‐linked hypopituitarism and neural tube defects. Issue 8 (15th April 2014) - Bauters, Marijke; Frints, Suzanna G.; Van Esch, Hilde; Spruijt, Liesbeth; Baldewijns, Marcella M.; Die‐Smulders, Christine E. M. de; Fryns, Jean‐Pierre; Marynen, Peter; Froyen, Guy
<x xml:space="preserve">Abstract</x> Genomic duplications of varying lengths at Xq26–q27 involving SOX3 have been described in families with X‐linked hypopituitarism. Using array‐CGH we detected a 1.1 Mb microduplication at Xq27 in a large family with three males suffering from X‐linked hypopituitarism. The duplication was mapped from 138.7 to 139.8 Mb, harboring only two annotated genes, SOX3 and ATP11C, and was shown to be a direct tandem copy number gain. Unexpectedly, the microduplication did not fully segregate with the disease in this family suggesting that SOX3 duplications have variable penetrance for X‐linked hypopituitarism. In the same family, a female fetus presenting with a neural tube defect was also shown to carry the SOX3 copy number gain. Since we also demonstrated increased SOX3 mRNA levels in amnion cells derived from an unrelated t(X;22)(q27;q11) female fetus with spina bifida, we propose that increased levels of SOX3 could be a risk factor for neural tube defects. © 2014 Wiley Periodicals, Inc.